Impact Of Proposed Commodity Transaction Tax On Futures Trading In India - Pravakar Sahoo; Rajiv Kumar (Indian Council for Research on International Economic Relations (ICRIER), 2008)
Trading in commodity derivatives on exchange platforms is an instrument to achieve price discovery, better price risk management, besides helping macro-economy with better resource allocation. Since the inception (2003) of national online trading on multi-commodity exchange platforms, the trade volumes have grown exponentially. In the union budget 2008-09, the government has proposed to impose a commodity transaction tax (CTT) of 0.017%. Though the stated rationale for imposing higher taxes is to contain price rise and volatility, to generate revenue, and to increase transparency, these arguments are debatable and not much rooted in the available literature. In this context, we examine the relationship between trading activity, volatility and transaction cost using a three-equation structural model for five top selected commodities namely Gold, Copper, Petroleum Crude, Soya Oil and Chana (Chickpea). Results suggest that there exists a negative relationship between transaction cost and liquidity, and a positive relationship between transaction cost and volatility. Therefore, if the government imposes CTT, it would lead to higher volatility and lower trading activity affecting market efficiency and liquidity. However, agricultural commodities such as refined Soya oil and Chana are least affected in terms of volume and volatility in response to the imposition of transaction tax. Increased volatility may lead to more speculative activity and fail to achieve the price discovery and resource allocation objectives of the commodity markets. Further, the granger causality results reveal the efficiency of futures markets but do not provide any conclusive evidence about the nexus between price rise and futures trading.
Keywords: G19; G13; G14; L71; Q40; 330; Commodity Transaction Tax; Futures Market; Liquidity; Volatility; Warenbörse; Rohstoffderivat; Finanztransaktionssteuer; Indien